[18F]Fluorodeoxyglucose-positron emission tomography/computed tomography response evaluation can predict histological response at surgery after induction chemotherapy for oligometastatic bladder cancer. (4th July 2017) - Kollberg, Petter; Almquist, Helen; Bläckberg, Mats; Cwikiel, Magdalena; Gudjonsson, Sigurdur; Lyttkens, Kerstin; Patschan, Oliver; Liedberg, Fredrik
Abstract: Objective: Patients with limited metastatic and locally advanced bladder cancer have a poor prognosis, and no definite treatment recommendations exist. However, long-term survival is possible for selected patients if surgery is combined with multiple courses of chemotherapy (i.e. induction chemotherapy). Patients with tumours that are insensitive to chemotherapy probably have little to gain from subsequent extensive surgery. The aim of this study was to evaluate sequential FDG-PET/CT examinations as an indicator of chemotherapy response. Materials and methods: Between 2007 and 2015, 50 patients with oligometastatic invasive bladder cancer selected for induction chemotherapy underwent two FDG-PET/CT examinations: the first before the start of chemotherapy and the second after three courses of cisplatinum-based combination chemotherapy. Responders were given up to six courses of chemotherapy. FDG-PET/CT response was correlated with histological response in excised lymph-node metastases. Results: Three patients showed progression to incurable disease during chemotherapy and another two patients did not undergo surgery, for medical reasons. Lymphadenectomy was performed in the remaining 45 patients, of whom 43 had lymph-node metastasis. FDG-PET/CT prediction of the histological nodal chemotherapy response was correct in 37 (86%) of those 43. The second FDG-PET/CT examination identified four out of nine non-responders. For response, the sensitivity, specificity, and positive and negative predictive values for FDG-PET/CT accuracy were 37 out of 37 (100%), one out of six (17%), 37 out of 42 (88%) and one out of one (100%), respectively. Conclusions: Repeated FDG-PET/CT seems to predict histological response. However, with the histological response criteria used in this study, five non-responders were not identified by the second FDG-PET/CT investigation.